Dimensão mágico-religiosa da palavra em textos orais sobre o catolicismo popular na comunidade São Domingos, Catalão-GO - (:unkn) unknown (Universidade Federal de Goiás, 2015)
This study aimed to understand in oral texts of a religious nature, of the São Domingos community in Catalão-GO, the magical-religious dimension of the words, which, in the view of subjects of research, has the power to influence the course of events. The material of study were composed by five narrative episodes, with six people, dwellers or former residents of the community, in a qualitative study of mixed character, which involved studies in office/laboratory and field. We assumed that the permeated linguistic events of popular religion, especially catholicism, would present a magical-religious dimension whose the elements external to language and resulting from agreements concluded by speaking community over time, could give, or not, the pragmatic meaning of the words or language constructions, with their power according to the context in which they perform. The recordings, transcripts, inventory and analysis of data, in lexicultural perspective (PESSOA, 2005; PINTO CORREIA, 2013; DURANTI, 2000 among others), revealed that the extra-linguistic universe of the subjects under study - the circumstances, the social conventions and the historical and cultural facts - that circumscribe the religious texts in their daily lives, participates in the construction of the meanings attributed to linguistic signs of field of the worldview of popular catholicism. Finally, the study corroborated the thesis that language is intrinsically related to the culture of a people, especially in its lexical configuration, where the cultural traits of a people are better evidenced (BIDERMAN, 1998; SOUZA, 2014). In this context, the words, as a key element of the practices analyzed in this study, is considered as a element of wisdom of human that, understood as action and medium of communication, acquires the power to act in the world, taking a magic-religious dimension.
Magical-religious dimension of the word in oral texts on the popular catholicism in São Domingos community, Catalão-GO
Keywords: Palavra; Catolicismo popular; Cultura; Dimensão mágico-religiosa; Words; Popular catholicism; Culture; Magical-religious dimension; LINGUISTICA, LETRAS E ARTES::LINGUISTICA